Genetic Engineering for Disease Resistant Crops: Sustainable Solutions for Agricultural Pathogens in Indonesia - Judijanto, Loso (Westscience Press, 2025)
Genetic engineering presents a transformative solution for addressing agricultural pathogens, offering disease-resistant crops that enhance productivity and sustainability. This study explores the potential of genetic engineering as a tool for combating agricultural challenges in Indonesia, employing a qualitative analysis of data collected from five key informants, including agricultural scientists, policymakers, and practitioners. Thematic analysis using NVIVO software revealed four primary themes: the benefits of genetic engineering, challenges in adoption, socio-economic impacts, and environmental considerations. Findings highlight the promise of reduced crop losses, improved food security, and decreased pesticide use while identifying barriers such as regulatory hurdles, public skepticism, and high costs. Recommendations emphasize policy reforms, public education, and equitable access to genetically engineered seeds. This study underscores the critical role of genetic engineering in achieving sustainable agriculture in Indonesia.